MARKETS IN CRYPTO-ASSETS AND CAPITAL MARKET - Cristian GHEORGHE (Challenges of the Knowledge Society)
Crypto-assets are defined as digital representations of value or of rights, applications of distributed ledger technology (DLT), including blockchain technology. DLT means an information repository that keeps records of transactions and that repository is shared across, and synchronised between, a set of DLT network nodes. Representations of value regarding crypto asset include a value attributed to a crypto-asset by the parties concerned or by market participants. That means the value is based on the interest of the purchaser of the cryptoasset only. Digital assets that cannot be transferred to other holders do not fall within the definition of crypto-assets. Therefore, digital assets that are technically impossible to transfer directly to other holders should be excluded from the scope of the European Regulation [Regulation (EU) 2023/1114]. Some crypto-assets qualify as financial instruments as defined in Directive 2014/65/EU of the European Parliament and of the Council1 (MiFID II) and fall within the scope of existing Union legislative acts on financial services. Therefore, a set of rules already applies to issuers of such crypto-assets and to firms conducting activities related to such crypto-assets. But other crypto-assets fall outside of the scope of Union legislative acts on financial services. European legislator chooses to regulate crypto assets that not fall within the regulation of financial instruments outside of this regulation. The new regulation [Regulation (EU) 2023/1114]2 intended to legislate in the field of crypto-assets, not interfering with financial instruments. Somehow similar to financial instruments market architecture the new regulation defines crypto assets types (e-money tokens, ‘asset-referenced tokens’ and third type outside the two defined types), admission to trading of crypto-assets and offer to the public of crypto assets, crypto-asset services and application for authorization as a crypto-asset service provider or operation of a trading platform for crypto-assets, prevention and prohibition of market abuse involving crypto-assets. Similar to capital market domain, Member States shall designate the competent authorities responsible for carrying out the functions and duties provided for in the regulation on crypto assets market. Member States shall notify those competent authorities to EBA (European Banking Authority) and ESMA (European Securities and Markets Authority).